Entrepreneurial Motivation as a Mediator of Financial Literacy, Family Environment, and Love of Money on Entrepreneurial Interest in Gen Z Students - Andi Anggi Kemalasari; Andika Isma; Soussou Raharimalala (PT Mattawang Mediatama Solution, 2025)
Entrepreneurial interest reflects an individual’s intention and willingness to engage in entrepreneurial activities, often driven by personal motivation and the courage to take calculated risks. Generation Z, born between 1995 and 2012, has grown up in the digital era, shaping their mindset and access to entrepreneurial opportunities. This study investigates the extent to which financial literacy, family environment, and love of money influence the entrepreneurial interest of Gen Z students, with entrepreneurial motivation acting as a mediating variable. A quantitative research approach was employed using primary data collected through questionnaires from 99 Gen Z students. Path analysis was conducted to test the proposed relationships. The findings reveal that financial literacy, family environment, and love of money each significantly influence entrepreneurial motivation, which in turn has a strong mediating effect on entrepreneurial interest. These results highlight the critical role of internal motivation in bridging cognitive, emotional, and contextual factors in the entrepreneurial decision-making process among Gen Z students. This study provides useful insights for educators and policymakers aiming to cultivate entrepreneurship among younger generations through targeted support in financial education, family engagement, and value orientation.